Analisis Model Implementasi Tracking Pengiriman Barang Menggunakan Waterfall dan Rapid Application Development - Achlison, Unang; Teguh Santoso, Joseph; Rozikin, Khoirur; Diapoldo, Fujiama (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
System Development Life Cycle (SDLC) is a common methodology used to develop information systems. The purpose of this study is to determine system development between the Waterfall and Rapid Application Development (RAD) models The advantage of using the waterfall method is that the quality of the resulting system will be good because the implementation is carried out in stages. The disadvantage of using the waterfall method is that the system development process takes a long time. The advantage of using the RAD Model method is that the integration of sensors/other applications can be processed faster and more effectively. The disadvantage of using the RAD method is the limitations of payment gateways, and chat bots.